Insight of ISA 701: Key Audit Matter disclosure in extended audit report? - Alshdaifat, Sajead Mowafaq; Abdul Hamid, Mohamad Ali; Saidin, Saidatunur Fauzi; Ab Aziz, Noor Hidayah (Human Resources Management Academic Research Society (HRMARS), 2024)
This review aims to present a comprehensive review of ISA 701 and relevant research on the disclosure of Key Audit Matters (KAM) in extended audit reports. This article is organized into five main streams: (1) Identification of Key Audit Matters; (2) Communication of ISA 701 regarding KAM; (3) The Informative Value of KAM; (4) Types of disclosed KAM; and (5) Opportunities and challenges related to KAM disclosure. The paper highlights the importance of KAM, emphasizing its benefits in enhancing transparency, reducing information asymmetry, improving decision-making processes, increasing the value relevance of information, and reinforcing stakeholder accountability. Conversely, it acknowledges the weaknesses and challenges associated with inconsistent disclosure of KAM, which may jeopardize users' investment decisions and potentially threaten financial statement users. This situation could result in heightened audit time, costs, and potential legal liabilities to auditors. The study contributes to the existing literature by summarizing and analyzing prior research findings. It offers insights into how the disclosure of Key Audit Matters (KAM) can impact audit quality, financial reporting, and the decision-making process for various stakeholders.